The Impact of Step Recommendations on Body Composition and Physical Activity Patterns in College Freshman Women: A Randomized Trial - Bruce W. Bailey; Ciera L. Bartholomew; Caleb Summerhays; Landon Deru; Sharla Compton; Larry A Tucker; James D. LeCheminant; Joseph Hicks (Journal of Obesity)
Purpose. Transitioning from high school to college generally results in reduced physical activity and weight gain at a rate that is higher than the general population. The purpose of this study was to examine the effects of three progressively higher step recommendations over 24 weeks on changes in body weight and body composition. Methods. Ninety-two freshmen college women wore a multifunction pedometer for 24 weeks after being randomly assigned to a daily step level: 10,000, 12,500, or 15,000. Pedometer data were downloaded every two weeks and participants were counseled on meeting their step recommendation. Body weight and body composition were assessed at baseline and 24 weeks. Body composition was assessed by dual X-ray absorptiometry. Results. On average, women took 10,786 ± 1501, 12,650 ± 2001, and 13,762 ± 2098 steps per day for the 10,000-, 12,500-, and 15,000-step groups, respectively (F = 15.48, P<0.0001). Participants gained 1.4 ± 2.6, 1.8 ± 2.1, and 1.4 ± 2.1 kg for the 10,000-, 12,500-, and 15,000-step groups, respectively (F = 37.74, P<0.0001). Weight gain was not significantly different between groups (F = 0.18, P=0.8385). There was also no difference in fat weight gain (F = 0.41, P=0.7954). Discussion. A step recommendation beyond 10,000 does not prevent weight or fat gain over the first year of college. Future research should focus on either intensity of physical activity or the addition of dietary interventions to prevent weight gain during the first year of college.